Man´s Attitude Towards Animals Within the Context of Gender, Age, Place of Living, Eating Habits, and Worldview in Slovakia - Kaliský, Ján; Kaliská, Lada (Studia Ecologiae et Bioethicae, 2022)
The ecological values or environmental competency development is currently an important topic. Attitude, relationship, love or respect for nature can be identified within several theories by various diagnostic tools, though they might be so general covering a man´s true attitude towards animals. The study discusses the characteristics of the author's questionnaire of human-animal relationship AniRe-Que (15) based on the ecological theory of biocentric egalitarianism covering extraterrestrial beings´ respect and consideration. The Questionnaire of Ecocentric and Anthropocentric Attitudes Towards the Environment (Thompson and Barton 1994) adapted by Siegrist (1996) was used to determine the construct validity of the author's questionnaire. Both tools were used to search for respondents' attitudes towards animals (N=937) in the context of their gender, age, residence, eating habits and worldview. The research study is of correlation-differential study design. The most important findings were that the attitude towards nature expressed in general does not completely coincide with the attitude towards animals leading to the hypothesis not all natural being are treated with equal respect by a man. The self-reported respect for animals was significantly lower than the respect for nature assessed by the ecocentric environmental attitude. The diagnostic tools thematizing only nature in its general (complex, synthesizing) context seem to be not sufficient to determine a respondent's attitude towards animals. A man might protect nature, but s/he can care less about the animals.